Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Stress Testing the Banking Sector. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Note discusses key results of stress testing of the banking sector in Austria. The Austrian banking system is in a recovery phase following the 2008-2009 global financial crisis. Stress testing results suggest that Austrian banks, on aggregate, have sufficient capital buffers to withstand severe but plausible shocks from adverse macroeconomic developments. Under the most severe scenario, the estimated total capital shortfall amounts to 1 percent of GDP. The results of the solvency stress test reflect comfortable initial capital buffers built in response to the crisis, in part because of de-risking of balance sheets, and in part owing to banks' recapitalization efforts through increased retained earnings.